Interpretation of modified glucose tolerance test in Malaysia population - Al-Kubaisi, Muna Khaleel Dheyab; Awang, Mokhtar; Ismail, Hamizah (2016)
Introduction Gestational diabetes is diagnosed by using different criteria. Basically O`Sallivan and Mahan implemented the used of 2 standard deviation from the mean in pregnant women in their late 2nd and early 3rd trimester. The result for the fasting and postprandial were 5 and 8.05 mmol/l respectively. The blood samples taken were whole blood. By 1982; Carpenter made a new work using the plasma to analyse blood glucose by the enzymatic method that is still in use. He found higher level for fasting and 2 hours postprandial, it was 5.3 and 8.6 mmol/l. The latest study regarding criteria for diagnosing GDM was the HAPO study using the postnatal outcome as an indicator; it recommended 5.1 mmol for fasting and 8.5 for 2h after 75g oral glucose. The Malaysian guideline diagnostic criteria for GDM is 5.6/7.8 mmol for the fasting and the 2h post 75g sugar.